Contributing Factors and Induced Outcomes of Psychological Stress Response in Stroke Survivors: A Systematic Review - Zhang, Song; Yuan, Yuan; Zhuang, Wenwen; Xiong, Tianqing; Xu, Yijun; Zhang, Jingwen; Tao, Chunhua; Liang, Jingyan; Wang, Yingge (Frontiers in Neurology, 2022)
Abstract Background: Remarkable evidence indicates that psychological stress is significantly associated with stroke. However, a uniform recommendation to identify and alleviate poststroke psychological stress responses and improve postmorbid outcomes is not currently available. Thus, this systematic review aimed to summarize the types of poststroke psychological stress, measurement tools, contributing factors and outcomes. Methods: This systematic review was undertaken in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses. A literature search was conducted in the PubMed, Web of Science, Embase, CNKI, WanFangData, and CQVIP, from database inception to November 2021. Cross-sectional and longitudinal studies were included in this research. Quality assessment was performed based on the National Institutes of Health (NIH) Quality Assessment Tool for Observational Cohort and Cross-Sectional Studies. Results: Eighteen quantitative, peer-reviewed studies were included for analysis. Selected articles mainly investigated perceived stress and posttraumatic stress disorder after stroke. We classified the contributing factors into four categories: sociodemographic factors, clinical disease factors, psychological factors, and behavioural and lifestyle factors. The postmorbid outcomes were divided into three categories: clinical disease outcomes, psychological outcomes, and behavioural and quality of life outcomes. Conclusions: Compared to common patients, stroke survivors with the following characteristics suffered an increased psychological stress response: younger age, the presence of caregivers, depression, unsuitable coping strategies, etc. Meanwhile, lower quality of life, worse drug compliance, worse functional independence, and more severe mental disorders were significantly associated with increased psychological stress symptoms. Further studies are required to provide more trustworthy and meaningful references for mitigating the damage caused by psychological stress after stroke.